From Waste to Energy: Sustainability Assessment of Rice Husk Biomass Power Generation - Trissa Silvian; Elisa Wildayana; Yunita (Journal of Global Sustainable Agriculture, 2025)
This study aimed to evaluate the sustainability status of rice husk waste processing as fuel for Biomass Power Plant (PLTBm) at PT Buyung Putra Pangan. The research was conducted in Ogan Ilir Regency, South Sumatra Province, from January to May 2023. The approach used was an expert preference approach through Focus Group Discussions (FGDs) involving various stakeholders. Data were analyzed using the Multidimensional Scaling (MDS) method integrated into the RAPFISH software, focusing on three sustainability dimensions: social, economic, and environmental. The results showed that the economic dimension was categorized as moderately sustainable (index 61.21), while the social (45.92) and environmental (38.56) dimensions were categorized as less sustainable. The average sustainability index of 48.56 indicates that the rice husk waste processing at PT Buyung Putra Pangan is generally in a less sustainable status. These findings highlight the need for improvements in sensitive attributes, particularly in managing environmental impacts and enhancing community outreach, to ensure that the rice husk processing aligns with sustainable development principles.